(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article examines the functionality of sexual violence in the context of the repression perpetrated in the Posadas Hospital du- ring the last military dictatorship in Argentina. Due to the visibility of this issue in the trial “Hospital Posadas II” in 2018, I start by analyzing the case of an ex-employee in the lactation area who suffered rape, to show that this was not an isolated event. On the contrary, it was a repeated practice inscribed within the broader disciplinary strategies that hospital workers had to endure in that period. Finally, I examine the actions of the penal justice system since the report of the crime, as well as the resignification of the case in the current context.